Data activism : Feminicidio.net and the mapping of femi(ni)cide in Europe - Luján-Pinelo, Aleida (Taylor & Francis, 2026)
In recent years, the study of femi(ni)cide (femicide/feminicide) has seen a surge in interest beyond Latin America and the Caribbean, accompanied by efforts to map feminist activism against femi(ni)cide, including data-driven initiatives. Although research on femi(ni)cide in Europe has gained more attention recently, comprehensive cartographies that account for how femi(ni)cide is being framed and addressed in Europe, including the mapping of femi(ni)cide data activism there, remain scarce. This article aims to bridge this gap by presenting a cartography of Geofeminicidio (Spain), the first comprehensive initiative to document femi(ni)cide in a European country, launched in 2010. Drawing on feminist epistemology of situated knowledges, biographical interview, and autoethnographic methodology, this paper traces the project’s roots in Latin American knowledge and activism. Based on semi-structured interviews with the project’s founder, Graciela Atencio, and complemented with analysis of other archival material, the article traces three major influences: personal lived experience, the ethics of the Mothers of Plaza de Mayo human rights movement in Argentina, and the documentation of femi(ni)cides in Ciudad Juárez in Mexico. This paper aims to contribute to regional and global debates on data activism related to femi(ni)cide.